2007
DOI: 10.1016/j.devcel.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Capu and Spire Assemble a Cytoplasmic Actin Mesh that Maintains Microtubule Organization in the Drosophila Oocyte

Abstract: SummaryMutants in the actin nucleators Cappuccino and Spire disrupt the polarized microtubule network in the Drosophila oocyte that defines the anterior-posterior axis, suggesting that microtubule organization depends on actin. Here, we show that Cappuccino and Spire organize an isotropic mesh of actin filaments in the oocyte cytoplasm. capu and spire mutants lack this mesh, whereas overexpressed truncated Cappuccino stabilizes the mesh in the presence of Latrunculin A and partially rescues spire mutants. Spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
225
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(251 citation statements)
references
References 47 publications
26
225
0
Order By: Relevance
“…Actin has been thought to play an inhibitory role in ooplasmic streaming because depolymerization of F-actin by latrunculin A or cytochalasin D (64,65) or mutations of the actin regulators chickadee, cappuccino, and spire (64-69) cause premature streaming. However, both of these drug treatments and actin regulator mutations abolish only the cytoplasmic actin meshwork in stage 9-10A oocytes, whereas the cortical actin filaments remain intact (62). We confirmed these data and found that even very high concentrations of latrunculin B (up to 100 μM) failed to decrease phalloidin staining at the cortex, suggesting that cortical actin filaments, just like immobilized cortical microtubules, are extremely stable during mid-to late oogenesis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Actin has been thought to play an inhibitory role in ooplasmic streaming because depolymerization of F-actin by latrunculin A or cytochalasin D (64,65) or mutations of the actin regulators chickadee, cappuccino, and spire (64-69) cause premature streaming. However, both of these drug treatments and actin regulator mutations abolish only the cytoplasmic actin meshwork in stage 9-10A oocytes, whereas the cortical actin filaments remain intact (62). We confirmed these data and found that even very high concentrations of latrunculin B (up to 100 μM) failed to decrease phalloidin staining at the cortex, suggesting that cortical actin filaments, just like immobilized cortical microtubules, are extremely stable during mid-to late oogenesis.…”
Section: Discussionsupporting
confidence: 79%
“…Besides microtubules, actin filaments play an important role in streaming. Two subsets of F-actin have been described in the oocyte cytoplasm during midto late oogenesis (stages 9-11): a transient cytoplasmic meshwork assembled at stage 9 and disassembled at stage 10B and a more stable layer of cortical actin filaments that persisted from stage 9 to stage 11 (62,63). Actin has been thought to play an inhibitory role in ooplasmic streaming because depolymerization of F-actin by latrunculin A or cytochalasin D (64,65) or mutations of the actin regulators chickadee, cappuccino, and spire (64-69) cause premature streaming.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pfender et al (2011) found that Spire 1 and 2, another type of actin nucleators, cooperate with formin-2 to nucleate actin filaments in mouse oocytes. In Drosophila oocytes, Spire and Cappuccino (the fly formin-2) are required for establishing oocyte polarity by organizing an actin network, although the precise function of the actin network differs from that present in mouse oocytes [Dahlgaard et al, 2007;Quinlan et al, 2007]. In vitro biochemical studies have also established the interactions of these two types of actin nucleators [Bosch et al, 2007;Quinlan et al, 2007], but it remains to be determined how formin-2 and Spire synergize in vivo to nucleate actin filaments.…”
Section: Spindle Migration: Where and How The Force Is Generatedmentioning
confidence: 99%
“…both induce premature ooplasmic streaming (5,6). Later it was shown that both proteins cooperate in the generation of a dynamic actin mesh in the oocyte that prevents premature ooplasmic streaming (7). Spire and Cappuccino do not solely have the same mutant phenotype; the proteins also physically interact and cross-regulate each other.…”
mentioning
confidence: 99%